Selection of the Optimal FBG Length for Use in Stress-Strain State Diagnostic Systems - Viktor Vikulov; Aleksandr V. Todorov; Aleksey V. Faustov; Nikolay L. Lvov (Civil Engineering Journal, 2019)
The article discusses fiber-optic sensors (FOS) based on the Bragg gratings for measuring systems for diagnostics of stress-strain state. Currently, such diagnostic systems are widely used in construction, industry and civil engineering. The physical principle of deformation diagnostics using FOS. The issues of mounting the sensor on the measured area (detail) are separately discussed. The principle of processing the hardware and software of sensors based on Bragg gratings is described. Research method - bench experiments that were carried out on an equal-deformation beam in order to evaluate the change in the width of the reflected FOS peak at different lengths recorded by the Bragg gratings in order to determine the optimal one. The change in the spectrum of the reflected peak under various deforming influences was monitored. Based on the results obtained, recommendations are made on the use of gratings of various lengths in the diagnostic systems for the stress-strain state of parts and assemblies for civil engineering tasks.